Analysis of Nepal Van Java Tourism Development Strategy During Covid-19 Pandemic - Sri Suwitri; Yuni Kurniasih; Rani Pajrin; R Yogie Prawira (Journal of Governance, 2023)
The tourism sector is one of the sectors that was most affected by the COVID-19 pandemic. The policy of social activities carried out by the government has an impact on the closure of tourist attractions. It has a direct impact on the sustainability of the area itself. One of the tourist attractions affected by COVID-19 is Nepal Van Java. It is located in Dusun Butuh, Temanggung Village, Kaliangkrik District, and Magelang Regency. The attractiveness is in the people's houses, which are very beautiful and interesting. In particular, this study aims to analyze regional tourism development strategies during the COVID-19 pandemic in the tourist area. The research method used is descriptive-qualitative. The results showed that the development and tourism strategy in Dusun Butuh started with analyzing its internal environment, namely promotion, accessibility, tourism area development, tourism products, human resources, and tourism awareness campaigns. Despite the various obstacles that have existed until now, such as the quantity and quality of human resources, accessibility to tourist sites, and insufficient public facilities, The strategy carried out by the manager in the regional tourism development strategy during the COVID-19 pandemic in Dusun Butuh has been quite effective. It is based on data on visitors from Nepal to Java in 2020, which continues to increase and can help local communities open additional businesses.